Palang Merah Indonesia Menjadi Salah Satu Organisasi Sosial di Masyarakat - Usiono Usiono; Annisa Aulia Hutasuhut; Shinta Apriani; Siti Qomariah Dalimunthe; Sri Ayuni (Peneliti.net, 2023)
This study aims to determine the perspective of the Indonesian Red Cross which is one of the social organizations in society as well as the tasks and objectives of PMI itself. The type of research used is descriptive qualitative research, namely a search aimed at describing and analyzing phenomena, events, social activities, attitudes, beliefs, perceptions, people's thoughts, individually or in groups with a focus on actual problems such as when the research was in progress. The results of the study show that PMI is a humanitarian organization with the status of a legal entity, which was promulgated by Law number 1 of 2018 concerning Red Cross Affairs in order to carry out Red Cross Affairs activities with the aim of preventing or avoiding and alleviating the suffering of prisoners of war victims and disasters without discriminate between religion, nation, ethnicity, skin color, class, gender, and political views. PMI which was established on September 17, 1945. PMI also has a performance that is still ongoing today, including: 1) Assisting during wars/conflicts, 2) Assisting victims of natural disasters, 3) Blood and health transfusions. PMI also has the task of turning PMI members into volunteers. Such as Volunteer Preparedness Assistance and Disaster Management First Aid Training for Volunteers, Public Health and Welfare Services and others